Erectile dysfunction: assessment and management in primary care. Issue 12 (19th June 2014) - Rajendran, Rajesh; Cummings, Michael
Abstract PDE5 inhibitors are the first‐line treatment for erectile dysfunction and allow management of ED in general practice. Here, the authors outline the causes, assessment and treatment options for this distressing condition.